Stages in the development of consumers' online trust as mediating variable in online banking system: a proposed model. (9th April 2019) - Chiu, Candy Lim; Chiu, Jason Lim; Mansumitrchai, Somkiat
Several studies suggest that consumers have not adopted online banking system to the same degree primarily because of online trust related issues. It is a long-term barrier for realising the potentials of B2C banking innovations. However, current literature relating to trust in online banking arguably falls short in at least two areas. First, lack of comprehensive study detailing the stages of trust as mediating variable between antecedents and consequence in order to understand consumers' online trust formation on self-service technologies. Second, most prior studies focus only on the general concept and effect of trust on consumer behavioural intention, adoption decision, and utilisation of innovations. This study tries to fill these gaps by systematically analysing online trust based on behavioural adoption models and technology acceptance theories as a fundamental prerequisite of B2C relationship in the retail industry, leading to the positive adoption of innovation.